Developing supplementary speaking material for the fifth grader of SDN Banjaranyar - Faridatunnisa, Ichda (Universitas Sarjanawiyata Tamansiswa, 2023)
The objectives of this study are, firstly, to develop supplementary speaking materials for the young learners in the fifth grade of SDN Banjaranyar and secondly, to describe the efficacy of the supplementary speaking material. This research belongs Rto esearch and Development (R&D) using simplified six steps of Borg and Gall’s model (1983). (1) Conducting need analysis, (2) Constructing the course grid, (3) Developing the Preliminary Material (4) Tryout of Preliminary Material, (5) Evaluation and revision by the experts, and (6) Final product. The findings showed that 1) the developed supplementary materials were to fulfill the students’ needs. The result of the need analysis was used to develop the supplementary materials. The content of the material was designed and based on the Preparation, Practice, and Production (PPP) approach. The developed supplementary speaking materials were distributed to experts to have the expert judgment to evaluate the product, 2) the efficacy of the developed supplementary speaking material helped students to experience an attractive and fun way of learning English so that they are more familiar with English to further have better confidence in using English. Furthermore, the developed speaking materials of this study provide appropriate learning activities for the fifth grader that suit their cognitive competence and needs.